Pengaruh Model Pembelajaran AIR Berbantuan Media Prezi Terhadap Keterampilan Menulis Teks Prosedur - Afi Nuraida; Lutfi Syauki Faznur (Politeknik Kampar, 2025)
The background of study was because of the low writing skills of seventh grade students in Indonesian language subject, specifically in Procedure Text. In addition, the lack of various learning models and media application affects the students' activeness and their understanding towards procedural text material during the learning process. The purpose of this study was to determine the effect of AIR (Auditory, Intellectually, Repetition) learning model with the help of Prezi media on the skill of writing procedure text. This research was conducted at SMP Muhammadiyah 22 Setiabudi Pamulang. This research uses experimental method with true experimental design and posttest-only control design. The result showed that AIR learning model influenced the procedure text writing skill of seventh grade. The findings was proved by the average posttest score in the experimental class which reached 82.50, while the average posttest score in the control class was only 67.72. Data analysis was conducted by calculating the Independent Sample t-test which showed the result of Sig. (2-tailed) results obtained 0.000> 0.05, then Ho is rejected and Ha is accepted. Based on the results of data analysis that has been completed, so it can be concluded that there is an effect of AIR (Auditory, Intellectually, Repetition) learning model assisted by Prezi media on procedure text writing skill in class VII.